2012
DOI: 10.1186/2251-6581-11-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the activates of antioxidant enzymes in red blood cells and body mass index in Iranian type 2 diabetes and healthy subjects

Abstract: BackgroundDiabetes mellitus is a metabolic disorder characterized by increased production of free radicals and oxidative stress. The aim of this study was to evaluate the activity of antioxidant enzymes, superoxide dismutase (SOD), glutathione reductase (GR), and glutathione peroxide (GSH-PX) in type 2 diabetic patients compared with healthy subjects.MethodsThis cross-sectional study was conducted on 100 type 2 diabetic patients and 100 healthy controls. Total antioxidant capacity and fasting serum levels of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 26 publications
2
17
0
3
Order By: Relevance
“…[47] There is a considerable body of evidence indicating that hyperglycemia may interfere with natural defense of the antioxidant system, in addition to increasing the production of free radicals. [48] Since SOD enzyme is part of the first line of defense against free radicals, it is expected that the activity of this enzyme may be affected by oxidative stress before the other antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[47] There is a considerable body of evidence indicating that hyperglycemia may interfere with natural defense of the antioxidant system, in addition to increasing the production of free radicals. [48] Since SOD enzyme is part of the first line of defense against free radicals, it is expected that the activity of this enzyme may be affected by oxidative stress before the other antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…[49] Taheri et al . [47] indicated that SOD activity was lower in patients with diabetes compared with healthy controls. There is evidence to show that hyperglycemia is accompanied by the loss of Cu 2+ , which is an essential cofactor in SOD activity, and SOD is inactivated by glycosylation in erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoid diketahui sebagai antioksidan yang baik karena mempunyai sedikitnya dua gugus hidroksil pada posisi orto dan para (Kuntorini, 2013). Antioksidan dapat mengikat radikal bebas (Taheri, 2012), dan membentuk kompleks dengan logam. Kedua mekanisme tersebut membuat flavanoid memiliki beberapa efek, diantaranya menghambat peroksidasi lipid, menekan kerusakan jaringan oleh radikal bebas dan menghambat aktivitas enzim glukokinase yang dapat memproduksi senyawa glukosa (Lukacinova, 2008).…”
Section: Hasil Pengukuran Kadar Glukosa Darah Metode Induksi Streptozunclassified
“…Kedua mekanisme tersebut membuat flavanoid memiliki beberapa efek, diantaranya menghambat peroksidasi lipid, menekan kerusakan jaringan oleh radikal bebas dan menghambat aktivitas enzim glukokinase yang dapat memproduksi senyawa glukosa (Lukacinova, 2008). Peningkatan enzim antioksidan berperan penting terhadap komplikasi diabetes dan resistensi insulin juga membantu dalammengurangistresoksidatif padapasien diabetes tipe 2 (Taheri, 2012).…”
Section: Hasil Pengukuran Kadar Glukosa Darah Metode Induksi Streptozunclassified
“…The main pathophysiological defect of type 2 diabetes is insulin resistance, a decrease in cellular response to insulin. Type-2 diabetes is manifested when pancreatic beta cells fail to compensate for chronic elevated blood glucose due to dysregulation of insulin-stimulated glucose uptake in the peripheral tissues (Taheri et al, 2012;Valiathan et al, 1998).…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%